Thinking Reflective Process of Student School First in Troubleshooting Reviewed From Learning Creativity - Awaludin, Aulia Ar Rakhman; Kurniawan, Indra; Hartuti, Purni Munah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The study aimed to describe the process of reflective thinking of students in solving mathematical problems in terms of the creativity of student learning high and medium categories. This type of research is qualitative. The qualitative method selected for determining the profile of reflective thinking of students in solving mathematical problems set in the natural and the main instrument is the researcher's own research. The results of the study obtained similarities and differences in students' reflective thinking processes are in high creativity and mathematical problem solving. During the preparation stage are the equation of student creativity and medium height, namely: the spirit of student responses when given KPM, after which students can express things that are known and asked is complete and correct. While the difference is high creativity Students understand the issues carefully. Differences reflective thinking processes and high creativity is about how students gather relevant information that will be used.